Effect of sowing time on growth and yield attributes of three mustard cultivars grown in Tidal Floodplain of Bangladesh (Journal of the Bangladesh Agricultural University, 2017)
The experiment was conducted at the field laboratory of the Patuakhali Science and Technology University, Patuakhali, Bangladesh during the period from November, 2011 to March 2012 under the tidal Floodplain region to find out optimum sowing time for the selected three cultivars (BARI Sharisha-15, BINA Sharisha-5 and BARI Sharisha-9). There were four sowing dates viz. 30 November, 15 December, 30 December and 15 January. Significant variations due to different sowing dates were observed in plant height, total dry matter, leaf area index, number of siliqua plant-1, seeds silique-1, 1000-grain weight, grain yield and HI. Results showed that the highest grain yield (1.73 t ha-1) was obtained from the first sowing (30 November) with BINA Sharisha-5 and it was significantly different from the yields of all other combination.J. Bangladesh Agril. Univ. 14(2): 155-160, December 2016